Процедури оцінювання діяльності службовців Корпусу оперативно-раптової дії - Путій, М. В.; Putii, M. V. (Юридичний бюлетень. - 2018. - Вип. 8. - С. 79-84, 2018)
Розглянуто основні особливості та критерії оцінювання суспільством діяльності правоохоронної системи України та такої важливої ланки правоохоронної системи, як спецпідрозділ Корпус оперативно-раптової дії. Розроблено та запропоновано авторську класифікацію критеріїв оцінювання службової діяльності спецпідрозділу, а саме: кількісні та якісні показники – стан виявлення, попередження та припинення адміністративних і кримінальних правопорушень; стан гарантування публічної безпеки і порядку під час проведення зборів, мітингів, походів, демонстрацій та інших масових заходів; убезпечення взятих під захист осіб, членів їхніх сімей, охорона адміністративних, державних будівель та інших об’єктів; стан управління й організації діяльності спецпідрозділу, ураховуючи визначені завдання та функції; оцінка кадрового потенціалу; рівень довіри населення.

In this article the main features and criteria of the society’s evaluation of the lawenforcement system of Ukraine and such an important part of the law-enforcement system as the special unit of the Operative-Rapid Action Corps are considered. The necessity and expediency of the development of a separate system for evaluating the activity of the Operational and Crisis Officer Staff was proved, taking into account the specifics of the activity of the unit and the functions performed: prevention, detection and termination of administrative and criminal offenses; ensuring public safety and order during meetings, rallies, campaigns, demonstrations and other mass events; security of the persons, members of their families taken into protection, protection of administrative, state buildings and other objects on the grounds and in the manner prescribed by the legislation of Ukraine; Participation in antiterrorist operations conducted in accordance with the Law of Ukraine “On the fight against terrorism”. It was emphasized that in most cases the activity of the special unit implies a narrowed direction of law enforcement activity, which is sometimes not even covered in the mass media and is not known to a wide circle of society. In such circumstances, when assessing the activities of the special unit, it is necessary to take a wide range of factors and factors that will be able to determine the effectiveness of the activities of the special unit. The author’s classification of the criteria for assessing the service activities of the special division has been developed and proposed, namely: quantitative and qualitative indicators – the state of detection, prevention and termination of administrative and criminal offenses; the state of ensuring public safety and order during meetings, rallies, campaigns, demonstrations and other mass events; security of the persons, members of their families taken into protection, protection of administrative, state buildings and other objects; the state of management and organization of the activity of the special unit, taking into account certain tasks and functions; assessment of personnel potential; level of public confidence.

Рассмотрены основные особенности и критерии оценивания обществом деятельности правоохранительной системы Украины и такого важного звена правоохранительной системы, как спецподразделение Корпус оперативно-внезапного действия. Разработана и предложена авторская классификация критериев оценки служебной деятельности спецподразделения
Procedures for assessing the activity of officers of the Operative-Sudden Action Corps
Keywords: Корпус оперативно-раптової дії; Corps of the Operative-Flash Action; Корпус оперативно-внезапного действия; КОРД; критерії оцінювання; evaluation criteria; критерии оценки; ефективність; efficiency; эффективность